Dukungan sosial teman sebaya dan kejadian ide bunuh diri pada mahasiswa - Moh Zamroji; Wita Oktaviana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Mental health is said to be good when the brain feels calm and relaxed, allowing a person to appreciate others and enjoy everyday life. People who have mental health are able to use all their potential to face obstacles in life and maintain positive relationships with other individuals. Based on data from the World Mental Health International College Student Project in 2018 which was conducted in 19 universities in eight countries, it showed that 35% of students experienced at least one DSM-IV mental disorder, such as mood, anxiety, and substance. A person's mental health, especially in the student group, is greatly influenced by peer social support which helps prevent the emergence of suicidal ideation. Purpose: To determine the relationship between peer social support and the incidence of suicidal ideation in students. Method: The type of quantitative research used a cross-sectional design, the sampling technique used the Slovin purposive sampling formula and obtained a sample of 244 respondents. The research instrument was a social support questionnaire consisting of 44 questions and a revised suite ideation scale (R-SIS) questionnaire consisting of 10 questions. Data analysis used univariate nonparametric correlation and bivariate Spearman's rho test. Results: Most respondents were 21 years old with a total of 129 respondents (52.9%), most were female with a total of 212 respondents (86.9%), and came from a nursing study program with a total of 100 respondents (41.1%). The social support obtained was high with a total of 206 respondents (84.5%) and most respondents did not have suicidal thoughts with a total of 237 respondents (97.1%). Based on the bivariate test, high social support made respondents not have suicidal thoughts with a total of 206 respondents (86.9%) with a p-value of 0.00 (<0.05). Conclusion: There is a relationship between social support (peers) and suicidal ideation. The negative correlation coefficient indicates that the level of suicidal ideation or desire tends to be higher when social support from peers is low. Conversely, if social support from peers is high, individuals tend not to make decisions that are detrimental to themselves, such as ending their lives. Suggestion: For students to be able to manage themselves by seeking various social supports from family, peers, lecturers and even from people they consider special. This serves to vent the emotions and burdens they experience, so as to avoid actions that are detrimental to others, especially themselves, such as consuming alcoholic beverages, drugs, and the emergence of suicidal ideation. Keywords: Peers; Social Support; Students; Suicidal Ideation. Pendahuluan: Kesehatan mental termasuk dalam taraf baik ketika otak merasa tenang dan santai yang memungkinkan seseorang menghargai orang lain dan menikmati kehidupan sehari-hari. Orang yang memiliki kesehatan mental mampu menggunakan semua potensi yang dimiliki untuk menghadapi rintangan dalam hidup serta menjaga hubungan yang positif dengan individu lainya. Berdasarkan data World Mental Health International College Student Project pada tahun 2018 yang dilakukan pada 19 universitas di delapan negara menunjukkan bahwa, sebanyak 35% mahasiswa mengalami paling tidak satu mental disorder DSM-IV, seperti mood, anxiety, hingga substance. Kesehatan mental seseorang terutama pada kelompok mahasiswa sangat dipengaruhi oleh dukungan sosial teman sebaya yang membantu mencegah ide bunuh diri. Tujuan: Untuk mengetahui keterkaitan dukungan sosial teman sebaya dengan kejadian ide bunuh diri pada mahasiswa. Metode: Jenis penelitian kuantitatif menggunakan desain cross sectional, teknik pengambilan sampel menggunakan purposive sampling rumus slovin dan didapatkan sampel sebanyak 244 responden. Instrumen penelitian berupa kuesioner dukungan sosial yang terdiri dari 44 pertanyaan dan kuesioner revised suicide ideation scale (R-SIS) berjumlah 10 pertanyaan. Analisis data menggunakan univariat dan bivariate uji nonparametric correlations spearman’s rho. Hasil: Mayoritas responden berusia 21 tahun dengan jumlah 129 (52.9%), sebagian besar berjenis kelamin perempuan sebanyak 212 responden (86.9%), dan berasal dari program studi keperawatan sebanyak 100 responden (41.1%). Dukungan sosial yang didapatkan tinggi sebanyak 206 (84.5%) dan sebagian besar responden tidak ada ide untuk bunuh diri sebanyak 237 (97.1%). Berdasarkan uji bivariate bahwa dukungan sosial yang tinggi membuat responden tidak memiliki ide bunuh diri sebanyak 206 (86.9%) dengan hasil p-value 0.00 (<0.05). Simpulan: Terdapat hubungan antara dukungan sosial (teman sebaya) dengan ide bunuh diri. Koefisien korelasi negatif menunjukkan bahwa tingkat ide atau keinginan untuk bunuh diri cenderung lebih tinggi ketika dukungan sosial dari teman sebaya rendah. Sebaliknya, jika dukungan sosial dari teman sebaya tinggi, individu lebih cenderung untuk tidak mengambil keputusan yang merugikan dirinya sendiri, seperti mengakhiri hidupnya. Saran: Bagi mahasiswa supaya dapat memanajemen diri sendiri dengan mencari berbagai dukungan sosial dari keluarga, teman sebaya, dosen pengajar bahkan dari orang yang dianggapnya spesial. Hal ini berfungsi untuk meluapkan emosi dan beban yang dialaminya, sehingga terhindar dari kegiatan yang merugikan orang lain terutama diri sendiri, seperti mengonsumsi alkohol, obat-obatan terlarang, dan munculnya ide bunuh diri Kata Kunci: Dukungan Sosial; Ide Bunuh Diri; Mahasiswa; Teman Sebaya.